Palliative care in patients with lung cancer - Farbicka, Paulina; Nowicki, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2013)
Lung cancer accounts for 12% of all cancers and has the highest annual rate of mortality in men and women. The overall aim is cure or prolongation of life without evidence of disease. Almost 60% of patients at the moment of diagnosis are not eligible for radical treatment. Therefore soothing and supportive treatment is the only treatment of choice. Patients with lung cancer who have symptoms of dyspnea, chronic cough, severe pain, exhaustion and cachexia syndrome, fear and depression and significantly reduced physical and intellectual activities are qualified for inpatient or home palliative care. Knowledge about various methods used in palliative treatment allows one to alleviate symptoms that occur in an advanced stage of disease with an expected short survival period. Methods of oncological treatment that are often used in patients with advanced lung cancer include radiotherapy and chemotherapy. Drawing attention to the earlier implementation of palliative care is an objective of research carried out during recent years. Advances in surgical and conservative treatment of these patients have contributed to better outcomes and longer survival time.